Copper-Induced Concomitant Increases in Photosynthesis, Respiration, and C, N and S Assimilation Revealed by Transcriptomic Analyses in Ulva Compressa (Chlorophyta) - Moenne-Munoz, A; Laporte-Poblete, D; Rodriguez-Tirado, F; Gonzalez-Figueroa, A (BioMed Central Ltd., 2020)
Background: The marine alga Ulva compressa is the dominant species in copper-polluted coastal areas in northern Chile. It has been shown that the alga tolerates micromolar concentrations of copper and accumulates copper at the intracellular level. Transcriptomic analyses were performed using total RNA of the alga cultivated with 10 μ M copper for 0, 1, 3 and 5 days using RNA-seq in order to identify processes involved in copper tolerance. Results: The levels of transcripts encoding proteins belonging to Light Harvesting Complex II (LHCII), photosystem II (PSII), cytochrome b6f, PSI, LHCI, ATP synthase and proteins involved in repair of PSII and protection of PSI were increased in the alga cultivated with copper. In addition, the level of transcripts encoding proteins of mitochondrial electron transport chain, ATP synthase, and enzymes involved in C, N and S assimilation were also enhanced. The higher percentages of increase in the level of transcripts were mainly observed at days 3 and 5. In contrast, transcripts involved protein synthesis and degradation, signal transduction, and replication and DNA repair, were decreased. In addition, net photosynthesis and respiration increased in the alga cultivated with copper, mainly at days 1 to 3. Furthermore, the activities of enzymes involved in C, N and S assimilation, rubisco, glutamine synthase and cysteine synthase, respectively, were also increased, mainly at days 1 and 3. Conclusions: The marine alga U. compressa tolerates copper excess through a concomitant increase in expression of proteins involved in photosynthesis, respiration, and C, N and S assimilation, which represents an exceptional mechanism of copper tolerance. © 2020 The Author(s).